A quantitative genetic analysis of leaf beetle larval performance on two natural hosts: including a mixed diet - Ballabeni, Pierluigi; Rahier, Martine (My University, 2001)
Published quantitative genetic studies of larval performance on different host plants have always compared performance on one host species or genotype vs. performance on another species or genotype. The fact that some insects may feed on more than one plant species during their development has been neglected. We executed a quantitative genetic analysis of performance with larvae of the leaf beetle Oreinaelongata, raised on each of two sympatric host plants or on a mixture of them. Growth rate was higher for larvae feeding on Adenostylesalliariae, intermediate on the mixed diet and lowest on Cirsium spinosissimum. Development time was shortest on A. alliariae, intermediate on mixed diet and longest on C. spinosissimum. Survival was higher on the mixed diet than on both pure hosts. Genetic variation was present for all three performance traits but a genotype by host interaction was found only for growth rate. However, the reaction norms for growth rate are unlikely to evolve towards an optimal shape because of a lack of heritability of growth rate in each single environment. We found no negative genetic correlations for performance traits among hosts. Therefore, our results do not support a hypothesis predicting the existence of between-host trade-offs in performance when both hosts are sympatric with an insect population. We conclude that the evolution of host specialized genotypes is unlikely in the study population.
Keywords: genetic correlation; larval performance; mixed diet; Oreina; reaction norm; trade-off